Correlation of myocardial fractional flow reserve with thallium-201 SPECT imaging in intermediate-severity coronary artery lesions - (:unkn) unknown (H M P COMMUNICATIONS, 2000)
Purpose. The purpose of this study was to compare the measurements of fractional flow reserve of the myocardium (FFRmyo) with results of quantitative coronary angiography (QCA) and stress single-photon emission computed tomography thallium-201 (SPECT Tl-201) imaging in patients with intermediate-severity coronary artery disease (ISCAD). Methods. We prospectively evaluated 40 lesions of QCA-determined ISCAD in 30 patients (age, 53.3 +/- 10.2 years; 67% male) using a 0.014 inch pressure wire during elective coronary angiography and compared the results with those of SPECT Tl-201 performed within a week of angiography. Results. There was a moderate negative correlation between percent diameter stenosis (%DS) and FFRmyo (53.1 +/- 13.4% and 0.75 +/- 0.09, respectively; r = -0.40; p = 0.01). Twenty-two out of 40 vascular territories (55%) were found to have perfusion defects (Group 1) and 18 territories (45%) were found to be normal (Group 2). While QCA-determined stenosis severity was not different between Group 1 and Group 2 (56 +/- 12% vs. 50 +/- 16%, respectively; p = 0.3), FFRmyo was found to be significantly different between the two groups (0.68 +/- 0.05 vs. 0.83 +/- 0.05, respectively; p = 0.001). When %DS and FFRmyo results were dichotomized as abnormal by greater than or equal to 50% and < 0.75, respectively, and SPECT Tl-201 was taken as the gold standard, sensitivity, specificity, positive predictive value and negative predictive value of %DS and FFRmyo were 0.55 vs. 0.91, 0.56 vs. 1.0, 0.60 vs. 1.0 and 0.50 vs. 0.90, respectively. Conclusion. While FFRmyo seems to accurately predict the presence of ischemia on SPECT Tl-201 in patients with ISCAD, QCA does not reliably assess the physiologic impact of the same lesions.
Keywords: coronary artery; intermediate-severity lesions; myocardial fractional flow reserve; thallium-201 SPECT imaging; VELOCITY RESERVE; PRESSURE MEASUREMENTS; GUIDE-WIRE; BLOOD-FLOW; ANGIOPLASTY; STENOSIS; DISEASE; HUMANS; REPRODUCIBILITY; HEMODYNAMICS